Análise das práticas e o processo de formação de professores de educação física: Implicações para a fundamentação da epistemologia da prática profissional - Rufino, Luiz Gustavo Bonatto [UNESP]; Benites, Larissa Cerignoni; Neto, Samuel De Souza [UNESP] (Univ Fed Rio Grande Do Sul, Escola Educ Fisica, 2017)
This study aimed to analyze and understand the possibilities for using Analysis of Practice (AP) strategies to build epistemology of professional practice, presenting some techniques and forms of use that could contribute to processes of Physical Education teacher training. Those strategies can help the analysis and development of teachers’ knowledge as well as become potential tools for both educational process and scientific research. Besides, they can also contribute to improve teachers’ work in. Physical Education and to value and strengthen their social legitimacy. Finally, it is very important that teachers understand that their actions create a diversity of knowledge that are often restricted to their private contexts. Thus, Physical Education can appropriate those strategies, integrating them into the set of actions allowing granting the practice the importance status it should have.
Analysis of practices and the process of physical education teacher education: Implications for the basis of the epistemology of professional practice
Análisis de las prácticas y el proceso de formación de profesores de educación física: Implicaciones para la fundamentación de la epistemología de la práctica profesional
Keywords: Education; Physical education and training; Professional education; Teaching